High Prevalence of Toxigenic and Nontoxigenic Clostridium difficile Strains in Malaysia - Riley, Thomas V.; Collins, Deirdre A.; Karunakaran, Rina; Kahar, Maria Abdul; Adnan, Ariza; Hassan, Siti Asma; Zainul, Nadiah Hanim; Rustam, F. R. Mohammed; Wahab, Z. Abd; Ramli, Ramliza; Lee, Yeong Yeh; Hassan, Hamimah; et al. (American Society for Microbiology, 2018)
Accumulating evidence shows a high prevalence of Clostridium difficile in Southeast Asia associated with a range of clinical presentations. However, severe infections are rarely reported. We investigated C. difficile infection (CDI) across four hospitals in Kuala Lumpur and Kota Bharu, Malaysia. Enzyme immunoassays for glutamate dehydrogenase (GDH) and toxin A or B were performed on diarrheal stool specimens collected from patients in 2015 and 2016. Specimens were also cultured and isolates of C. difficile characterized by PCR ribotyping and detection of toxin genes. In total, 437 specimens were collected and fecal toxin was detected in 3.0%. A further 16.2% of specimens were GDH positive and toxin negative. After culture, toxigenic strains were isolated from 10.3% and nontoxigenic strains from 12.4% of specimens. The most prevalent PCR ribotypes (RTs) were RT 017 (20.0%) and RT 043 (10.0%). The high prevalence of RT 017 and nontoxigenic strains in Malaysia and in neighboring Thailand and Indonesia suggests that they localize to the region of Southeast Asia, with an implication that they may mediate the burden of CDI in the region.